2014
DOI: 10.14257/ijhit.2014.7.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Information System of Yadnya Ceremony on Android-Based

Abstract: Implementation of very large religious ceremonies in Bali demanded Hindus to be able to understand things related to Yadnya ceremony. One of the reasons why people are reluctant to participate in the Yadnya ceremony is because they does not know how to execute the ceremony. A way that can be taken is to design and make a model of the system that presented the Yadnya ceremony through Android-based information systems. The system will provide information related to activities such as execution time of Yadnya cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
3
0
3
Order By: Relevance
“…Teknologi zaman sekarang yang paling populer dan berkembang yaitu perangkat mobile. Perangkat mobile yang memiliki beragam fitur menarik di dalamnya meliputi multimedia, games, hingga internet [2].…”
Section: Rancang Bangun Game Mobile Bola Adil Berbasis Android Denganunclassified
“…Teknologi zaman sekarang yang paling populer dan berkembang yaitu perangkat mobile. Perangkat mobile yang memiliki beragam fitur menarik di dalamnya meliputi multimedia, games, hingga internet [2].…”
Section: Rancang Bangun Game Mobile Bola Adil Berbasis Android Denganunclassified
“…Web-based Bebayuhan Oton information system gave the information about the process of Bayuh Oton ceremony with the necessary banten used, however it still uses only photos and text captions [8]. Tree data structure has been used for modelling on making Android based information systems about Yadnya ceremony [9], as well as Ulam Bebantenan [10]. The learning media for making upakara for the Nyiramin Layon procession is designed based on Android by displaying 3-dimensional objects, photos and videos [11].…”
Section: Introductionmentioning
confidence: 99%
“…The Balinese calendar also has an important role in carrying out Hindu religious ceremony day and can also search for birthdays and determine one's personal characteristics [4]. Of course not everyone knows the timing of the ceremony, so that Bendesa Adat is needed which specifically coordinates in the religious field in the village [5].…”
Section: Introductionmentioning
confidence: 99%
“…The result of user's satisfaction calculations from the distributed questionnaires is as follows From the results of the questionnaire distributed about the use of application to 30 people can be concluded that 0% of the public expressed very dissatisfied and dissatisfied, 32% of the respondents expressed quite satisfied, 54% of the respondents expressed satisfied and 14% expressed very satisfied. Compared to other research studies, this research is more specified in villagers' needs such as the events that will be held in the village [5]. This research can also provide information about the Dewasa Ayu of the funeral and marriage ceremony [11].…”
mentioning
confidence: 99%